Pemanfaatan Limbah Kulit Jengkol sebagai Bahan Baku Kompos dan Biochar dalam Meningkatkan Pertumbuhan dan Produksi Tanaman Bawang Merah (allium ascalonicum L.) - Naimat Hidayah Hasibuan; Sumihar Hutapea; Abdul Rahman (Universitas Medan Area, 2022)
The Waste Utilization Of Jengkol Peel As Raw Material Compost And Biochar In Increasing Growth And Production Of Onion (Allium Ascalonicum L.). Guided by Dr.Ir. Sumihar Hutapea, MS and Ir.H.Abdul Rahman, MS. This research aimed to determine effect of giving compost jengkol peel on the growth and production of onion, effect of giving biochar jengkol peel on the growth and production of onion, and effect of the combination between compost and biochar waste of jengkol peel on the growth and production of onion (Allium ascalonicum L.). This research was conducted in the House Kasa Growth Centre Kopertis Region I North Sumateta-Nanggroe Aceh Darussalam from April until September 2016. The research was conducted by planting in polybags with soil weight 5 kg/polybag. This research was conducted by using Randomized Block Design (RBD) factorial with 2 factors treatment. The first factor is compost of jengkol peel that consists of 4 levels dose are : K0 = (control), K1 = (10 ton/ha or 25 g/polybag), K2 = (20 ton/ha or 50 g/polybag), K3 = (30 ton/ha or 75 g polybag). The second factor is biochar of jengkol peel that consists of 4 levels dose are : B0 = (control), B1 = (5 ton / ha or 12.5 g / polybag), B2 = (10 ton / ha or 25 g / polybag), B3 = (15 ton / ha or 37.5 g / polybag). The results of research showed that treatment of jengkol peel compost was very significant effect on plant height at of 2 and 3 MST observation, significant effect on the observation aged 4 and 5 MST, and it is not affected real to the age of 6 MST observation. To the observations on the number of leaves on the age of 2, 3 and 4 MST is very significant effect, significant effect on the age of 5 MST observation and not affected real on the age of 6 MST observation. On the number of cloves and tuber diameter is not affected real. Fresh weight of tuber and dry weight of tuber is significant effect. Treatment of jengkol peel biochar is not affected real on all parameters of observation. Interaction treatment of compost and biochar of jengkol peel is significant effect on leaf length 2 and 3 MST, number of leaf age 2 MST and it is not affected real on other parameters.